Historical-critical pedagogy and its possibilities for the teaching of literature - Posenti, Ana Paula; Neto, José de Souza; Benites, Victória R. Dall’Apria (Seven Editora, 2023)
This paper aims to present the contributions of Historical-Critical Pedagogy and Cultural Historical Psychology in the process of teaching and learning for children in early childhood education. A work like this is justified by the conception that the Historical-Critical Pedagogy has about the teaching and learning process, that is, that seeks to expand the possibilities of the learner, about the use of what is richest and most important in the sciences and arts. In this case, what we will treat is the literature focusing on the development and appropriation of values. To this end, this work used the bibliography as the basic source of the research, especially the texts in which it deals with the methodology in the classroom, the Cultural Historical psychology and the children’s literature anchored to the Historical-Critical Pedagogy. Using as authors: Demerval Saviani, Vygotsky, Gasparin and others, who were of paramount importance for the theoretical foundation of the work. The result achieved with this research was the understanding of the main concepts in relation to the importance of teaching literature and how it can assist in child development, as well as the appropriation of concepts and the learning of infants, based on the principles of Saviani’s theory. We understand the importance of a teaching that allows, through knowledge, the emancipation of the student and social transformation. Given that the Dialectical Methodology of Knowledge Construction is the way for this emancipation to occur, from primordial concepts for development, adding Vygosky’s vision of such development, which is acquired through relations with the environment and with the social. In addition, we understand that the role of children’s literature is essential for the intellectual and critical maturation of the infant. Through readings guided by the mediator, it is possible for the reader to experience the process of catharsis, that is, to have their own findings, internalize the reading content and appropriate it, thus creating a new worldview. DOI:https://doi.org/10.56238/uniknowindevolp-103